Comparison of Outcome Between Ligation of Inter Sphincteric Fistula Tract with Distal Bipolar Electrocauterization (Lift With DBE) V/S Fistulectomy/ Fistulotomy for Fistula in Ano - Akram, Naseem; Verma, Rajkumar; Purohit, Saurabh (National Journal of Medical Research, 2025)
Background: Fistula-in-ano, an abnormal tract between the anal canal and perianal skin, often requires surgical management to prevent complications like abscesses, pain, and discharge. This study compares the outcomes of Ligation of the Intersphincteric Fistula Tract with Distal Bipolar Electrocauterization (LIFT with DBE) and traditional Fistulectomy/Fistulotomy. The study aims to evaluate the effectiveness of LIFT with DBE versus Fistulectomy/Fistulotomy in terms of fistula closure rates, recurrence, postoperative complications, healing, and recovery. Material and methods: A prospective study of 100 patients with fistula-in-ano was conducted. Patients were divided into two groups: Group-A (Fistulectomy/Fistulotomy) and Group-B (LIFT with DBE). Outcomes included recurrence, postoperative pain (Visual Analogue Scale), bleeding, incontinence, healing time, hospital stay, and time to resume normal activities. Statistical analysis was performed using SPSS. Results: Group-B (LIFT with DBE) had a significantly lower recurrence rate (10% vs. 20%) and a faster mean return to normal activities (11.6±1.750 days vs. 12.8±1.841 days) compared to Group-A. Postoperative pain, bleeding, and hospital stay were also more favorable in Group-B. There was no significant difference in fecal or flatus incontinence between the groups. Conclusion: LIFT with DBE demonstrated superior outcomes, including lower recurrence rates and quicker recovery, compared to Fistulectomy/Fistulotomy. It is a less invasive and more effective surgical option for fistula-in-ano, warranting further research into minimally invasive techniques.